Preventive Effect of Gonggan (Citrus Reticulata Blanco Var. Gonggan) Peel Extract on Ethanol/HCl-Induced Gastric Injury in Mice via an Anti-oxidative Mechanism - Ya Wu; Ya Wu; Ya Wu; Ya Wu; Hua Jiang; Guangfang Chen; Xingxing Chen; Chengming Hu; Xiaofei Su; Fang Tan; Xin Zhao; Xin Zhao; et al. (Frontiers Media S.A., 2021)
Gonggan (Citrus reticulata Blanco var. gonggan) is one of the most popular citruses. In this study, the effect of Gonggan peel extract (GPE) on gastric injury was investigated. The components in GPE were analysed by HPLC and the gastric injury model in mice was established by ethanol/hydrochloric acid. After treatment by GPE, the pathological changes of gastric tissue were observed by optical microscope. The levels of oxidative stress and inflammation were measure by kit. And the mRNA expression of related gene was determined by qPCR assay. HPLC result showed GPE mainly contained the flavonoids narirutin, hesperidin, nobiletin, tangeretin and 5-demethylnobiletin. Morphological and pathological analysis of gastric tissue revealed that GPE could relieve gastric injury. Also, GPE increased the levels of SOD, GSH-Px, and CAT and decreased the level of MDA. Moreover, GPE decreased the levels of the inflammatory cytokines TNF-α, IFN-γ, IL-1β, and IL-6 to suppress inflammation. In addition, the q-PCR results showed that GPE upregulated the mRNA expression of SOD1, SOD2, γ-GCS, GSH-Px, CAT, and IκBα and downregulated the mRNA expression of NF-κB. In conclusion, GPE alleviated gastric injury caused by ethanol/hydrochloric acid by inhibiting oxidative stress and the inflammatory response. The mechanism by which GPE protects gastric tissues may involve the antioxidative pathway. Therefore, GPE has great potential to be developed as a product to prevent gastric injury.